Pengaruh Talent Management dan Knowledge Management Terhadap Employee Performance dengan Employee Engagement Sebagai Variabel Intervening pada Pegawai Kantor Dinas Perumahan Rakyat Kabupaten Ende - Herman Y. F. Teku; Rafael Oktavianus Byre; Hyronimus Hyron (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human resource management has developed far from before, which currently carries out more strategic functions than administrative functions. One of the strategic functions of human resources in the organization is to prepare human resources or talents in the organization who have the capability and potential to support the achievement of organizational strategy. One of the determinants of high and low employee performance is determined by employee engagement factors. One form of effort from the organization to retain employees in the organization is by implementing Talent Management and Knowledge Management. Organizations today expect to have human resources in a superior group (talented employees). So that there is a need from the organization to maintain the talent owned by the organization in the talent management strategy. One of the efforts to acquire, develop and retain talented employees is through talent management. Another human resource management strategy in improving employee performance and employee engagement can also be obtained with knowledge management is to manage employee knowledge in the organization as efficiently and effectively as possible. Every organization needs to realize that the knowledge possessed in the organization can be the basis for organizational development.